2020
DOI: 10.1186/s12936-020-03261-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and clinical impact of malaria infections detected with a highly sensitive HRP2 rapid diagnostic test in Beninese pregnant women

Abstract: Background While sub-microscopic malarial infections are frequent and potentially deleterious during pregnancy, routine molecular detection is still not feasible. This study aimed to assess the performance of a Histidine Rich Protein 2 (HRP2)-based ultrasensitive rapid diagnostic test (uRDT, Alere Malaria Ag Pf) for the detection of infections of low parasite density in pregnant women. Methods This was a retrospective study based on samples collected in Benin from 2014 to 2017. A total of 942 whole blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Therefore, this suggests that uRDTs do not provide added benefits to the detection of infections among febrile individuals in the community when compared to regular RDTs, a finding that has been similarly observed among febrile outpatients in Tanzania [ 27 ]. Similarly, studies conducted among pregnant women observed a higher performance of uRDTs among afebrile women compared to febrile ones [ 28 , 30 ]. These studies were conducted under laboratory conditions using retrospectively collected samples [ 28 30 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, this suggests that uRDTs do not provide added benefits to the detection of infections among febrile individuals in the community when compared to regular RDTs, a finding that has been similarly observed among febrile outpatients in Tanzania [ 27 ]. Similarly, studies conducted among pregnant women observed a higher performance of uRDTs among afebrile women compared to febrile ones [ 28 , 30 ]. These studies were conducted under laboratory conditions using retrospectively collected samples [ 28 30 ].…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, studies conducted among pregnant women observed a higher performance of uRDTs among afebrile women compared to febrile ones [28,30]. These studies were conducted under laboratory conditions using retrospectively collected samples [28][29][30]. However, there is currently no evidence of the performance of uRDTs among pregnant women when the tests are directly conducted at point of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hoped that with this increased sensitivity, uRDTs would be able to detect enough asymptomatic infections to extrapolate total infection rates based on statistical modeling. The Alere Ultrasensitive Ag Pf RDT is now commercially available and has been tested in a number of field trials in different transmission settings (35)(36)(37)(38)(39)(40)(41)(42)(43) (Table 3).…”
Section: Ultrasensitive Rapid Diagnostic Tests (Urdts)mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors flagged that there is an error present in Table 5.…”
Section: Correction To: Malar J (2020) 19:188101186/s12936-mentioning
confidence: 99%